Bài toán tương đương ngôn ngữ trên lưới Petri suy rộng - Chau, Tran Tho (Journal of Computer Science and Cybernetics, 2018)
In this paper, we show that the equality problem for the languages generated by two self-modifying nets N1 and N2 is undecidable, and the equality problem for the sets of firing sequences of two self-modifying nets with two unbounded places under homomorphism is too undecidable.